Vascular reconstruction combined with liver resection for malignant tumours. Issue 13 (December 2013) - Azoulay, D.; Pascal, G.; Salloum, C.; Adam, R.; Castaing, D.; Tranecol, N.
<x xml:space="preserve">Abstract</x> Background The resectability criteria for malignant liver tumours have expanded during the past two decades. The use of vascular reconstruction after hepatectomy has been integral in this process. However, the majority of reports are anecdotal. This is a retrospective analysis of the techniques, morbidity, mortality and risk factors of liver resections with vascular reconstruction based on a large series from a single centre. Methods Patients who underwent hepatic resection combined with vascular resection and reconstruction between 1997 and 2009 were included in this study. Indications for surgery, morbidity and 90‐day mortality are reported along with factors predictive of operative mortality. Results Eighty‐four patients had liver resection with 97 vascular resections and reconstruction. There were 44 men and 40 women with a mean(s.d.) age of 56·9(12·1) years. Mean(s.d.) follow‐up was 37·3(34·1) months. All patients had primary or metastatic liver tumours. The perioperative morbidity rate was 62 per cent (52 patients) and the operative mortality rate 14 per cent (12). Predictors of operative mortality were: bilirubin level exceeding 34 µmol/ml (P = 0·023), indocyanine green retention rate at 15 min over 10 per cent (P = 0·031), duration of ischaemia (P = 0·011), amount of blood transfused (P = 0·025) and combined major extrahepatic procedure (P = 0·042). Actuarial 3‐ and 5‐year survival rates were 44 and 26 per cent respectively. Conclusion Liver resection with combined vascular resection and reconstruction can be performed in selected patients with acceptable morbidity and mortality. The lack of therapeutic alternatives and the poor outcome of non‐operative management seem to justify this approach. The identification of risk factors should help improve patient selection and postoperative outcome as well as facilitate objective risk communication with surgical candidates.